Thermodynamic analysis in laminar falling film evaporator. (September 2022) - Mahamoudou, Arnat; Ramousse, Julien; Cellier, Nicolas; Le Pierrès, Nolwenn
Highlights: 2D analysis of heat transfer in a laminar falling film evaporator. The sources of irreversibilities were identified, located and quantified. The local entropy generation varies with the operating and design conditions. The overall entropy generation is impacted by the local one. The thermal and evaporation efficiencies also impact the overall entropy generation. Abstract: An evaporative laminar falling film flowing by gravity on a vertical plate heated by a heat transfer fluid is studied to determine the local temperature, entropy generation and evaporated mass flow, assuming constant saturation pressure at the free interface, in co-current and counter-current configurations. The heat transfer fluid and film energy equations are solved simultaneously through a 2D model using an implicit finite difference scheme. Local and global analysis were performed in order to study the impact of parameters such as the heat transfer fluid and film Reynolds numbers and inlet film temperature on entropy generation (thermal and viscous irreversibilities) and on thermal and evaporation efficiencies. Results show that the increase of the overall thermal entropy generation leads to the increase of the evaporated mass flow rate. Both increase with the increase of the heat transfer fluid Reynolds number and decreases with the increase of the film Reynolds number for both configurations. The inlet film temperature – overheated or subcooled inlet fluid flow - also impacts the evaporation process. The influence of the Reynolds number and temperature difference on the heat transfer coefficients of both fluids and for both configurations is also discussed.